Implementing mental health in practice : strategies to engage patients and families. Inattention and impulsivity - Bauer, Nerissa S.; American Academy of Pediatrics ([Elk Grove Village, Illinois] : American Academy of Pediatrics, 2015)
This video focuses on using motivational interviewing techniques to identify and address inattention and impulsivity. In the case demonstrated, Tim is an 8-year-old boy accompanied by his mother to his pediatrician's office. He is always bothering other children in his classroom. There are 30 other children in his class. His mother believes that Tim is quite bright but he is not learning well in his classroom. He is about to fail math, reading, and science-although he particularly likes science. His teacher says he cannot work in a group, which is part of the science activities, without upsetting other members. His mother feels that he is a spirited child who is "just like his dad". She is reluctant to consider medication because she feels that the school environment is a large part of his learning and behavioral difficulties, but she's not sure how to help him if the school is unwilling to change.
Presenter: Nerissa S. Bauer.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 19, 2020)
Keywords: Attention-deficit-disordered children -- Behavior modification; Attention-deficit hyperactivity disorder; Documentary films; Educational films; Nonfiction films; Internet videos; Streaming video; Short films